Preliminary Study on the Development of Project Based Learning Inorganic Chemistry Practical Instructions - Eka Ad'hiya; Maefa Eka Haryani; Rodi Edi; K Anom W (Universitas Islam Indonesia, 2023)
This study aims to conduct a preliminary study in developing project-based learning practicum instructions in Inorganic Chemistry courses. This study uses a survey method, where data is obtained by conducting a survey through the Google form platform. Participants in this study were 41 students who took inorganic chemistry courses at the chemistry education study program at Sriwijaya University. The results of this study indicate that it is necessary to develop project-based learning practicum instructions for inorganic chemistry, as teaching materials in inorganic chemistry courses that apply project-based learning models in the current new normal era. The characteristics of students show that students feel happy, more motivated and feel more creative when participating in project-based learning.